Women “Having It all”: Family versus Work a Case Study in a Norwegian Company in Brazil - Cortese Coelho, Magdalena; Irene Häyrén, Anneli (Organizações & Sociedade, 2023)
We investigate the relationship between parentality and careers in a Norwegian corporation in Brazil, and using Joan Acker’s theory Gendered Organizations, we study how parental life could affect work life. Acker’s framework, especially Process 4: ‘the internal mental work of individuals making sense of their place and opportunities in the gendered organization’ is useful on societal, organizational and individual levels. We develop the framework by comparing men’s and women’s mental work regarding parentality and career opportunities. Results show that women want longer leaves, knowing that maternity is an obstacle. Men do not want longer father leave, and do not see fatherhood as obstacle. However, women agree with men about the company being supportive of their family life. We question the idea of “choices” for women since maternity is central when obstacles to careers are analyzed. Discrimination is blunt; women see it, even if they do not know how exactly it works. “Having it all” is a central theme of lack of satisfaction for women, in Brazil as elsewhere. Exporting gender equality in the context of this multinational company might be more an expectation, perception and/or myth than a reality, despite the current official statements. An analysis based on Acker and Brazilian authors point to the need of approaching organizations/careers x family considering e.g. parentality and care work, rather than maternity only. This work offers practical contributions to the diversity discussion and we suggest, for further studies, inclusion of e.g. race/ethnicity, sexual orientation, and class.